INVESTIGATING LISTENING AND SPEAKING CHALLENGES LEARNERS: ANALYZING EFL STUDENTS IN THE ENGLISH LANGUAGE TEACHING FIELD AT MILLAT UMIDI UNIVERSITY (American Journal of Pedagogical and Educational Research, 2026)
This study investigates the listening and speaking challenges faced by EFL students in the English Language Teaching (ELT) field at Millat Umidi University. Using a mixed-method approach, the research combines performance-based tasks with self-reported survey data to identify both observed and perceived difficulties. For listening, participants completed a comprehension task followed by a Likert-scale questionnaire addressing perception, parsing, and utilization problems. For speaking, students engaged in a role-play activity and subsequently reflected on their performance through an agree–neutral–disagree survey.The findings reveal that while learners demonstrate relatively fewer issues with perception (20%) and parsing (10%), all participants (100%) experience difficulties at the utilization stage, indicating challenges in interpreting and applying meaning. In speaking, the most significant problems include idea generation (90%), vocabulary and grammar (70%), and fluency and interaction (50%). The results suggest that learners struggle more with higher-order language processing, such as generating ideas and responding spontaneously, rather than basic language recognition or sentence formation.Overall, the study highlights the need for instructional approaches that prioritize communicative competence, critical thinking, and real-time language use to effectively address EFL learners’ difficulties.